Pengembangan Media Pembelajaran Interaktif Berbasis Power Point dalam Teknik Pembelajaran Passing Bawah pada Materi Bola Voli SMP Negeri 2 Lubuklinggau - Sulistiowati, Endang; Suhdy, Muhammad; Supriyadi, Muhammad (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This study aims to develop PowerPoint-based interactive learning media in the technique of passing under volleyball material. The research method used by ADDIE with five steps, namely 1) Analysis , 2) Design , 3) Development, 4) Implementation, 5) Evaluation. Data collection techniques observation, interviews, questionnaires. The data analysis technique used validity analysis with 3 experts, media expert validity analysis 0.84, language validity analysis 0.84, material validity analysis 0.89 so that what was obtained from the 3 media experts developed was very valid, then practical analysis by testing athletes with a one to one test getting a score of 81.21%, small group getting a score of 80.40% and coaches getting a score of 85.88% so that the media made is very practical, then analyzing the effectiveness by doing a pre test and post test as well as observations on students of SMP Negeri 2 Lubuklinggau for the pre test of 33 students only 1 student who fit the criteria and for the post test of 32 students only 31 students who fit based on the observation sheet. Keywords: Volleyball, Development, Interactive Powerpoint